Thermo-optical, structural, and morphological characterization of ZnO:PQX composite thin films - Nosidlak, Natalia; Wojtasik, Katarzyna; Dulian, Piotr; Szymczak, Patryk; Piz, Mateusz (Bulletin of the Polish Academy of Sciences Technical Sciences, 2026)
This work presents a detailed study of thin zinc oxide (ZnO) films and ZnO composite films doped with the organic luminescent dye PQX, prepared by the sol-gel method and spin coating. The optical, thermo-optical, structural, and morphological properties of these films were investigated using spectroscopic ellipsometry, X-ray diffraction, thermal analysis, atomic force microscopy, and scanning electron microscopy. The PQX dye showed strong absorption in the blue region of the spectrum with a large Stokes shift, indicating potential for luminescent solar concentrator (LSC) applications. Thermal studies revealed limited stability of PQX in thin films with partial degradation beginning at 100°C and complete decomposition above 300°C, which affected the optical and structural properties of the composite films. Annealing led to an amorphous state transition of the organic component and increased porosity in the ZnO matrix. ZnO:PQX films exhibited increased surface roughness and reduced refractive index compared to pure ZnO. These findings suggest that while PQX enhances certain optical properties, its thermal instability limits the performance of ZnO:PQX composites in LSC devices, highlighting the need for further materials optimization.